Post treatment for precise size and shape control of monodisperse CsPbBr₃ nanocrystals under ambient condition using ZnBr₂ - Foo, Di Kai (2023)
A mixed passivation strategy is deployed to produce monodisperse and pure CsPbBr3 nanocrystals under ambient condition via post treatment using ZnBr2 in mixed organic solvents. This room temperature synthesis route provides precise size and shape control, and colloidal nanocubes or nanospheres can be obtained depending on the choice of organic solvents. Any secondary phases' nucleation was inhibited. The ZnBr2 can reduce the Br- vacancies at the surface termination layers, thus enhancing their properties. This approach can potentially offer a cheap and viable route for perovskite nanocrystals in optical and electrical devices.